The spatial and temporal regulation of the hormonal signal. Role of mitochondria in the formation of a protein complex required for the activation of cholesterol transport and steroids synthesis - Poderoso, Cecilia (2013)
The mitochondria are critical for steroidogenesis since the ability of cholesterol to move into mitochondria to be available for cytochrome P450, CYP11A1, determines the efficacy of steroid production. Several proteins kinases, such as PKA, MEK and ERK which are essential to complete steroidogenesis, form a mitochondria-associated complex. The protein-protein interactions between kinases and key factors during the transport of cholesterol takes place in the contact sites between the two mitochondrial membranes; however, no mitochondrial targeting sequence has been described for these kinases. Here we discuss the possibility that mitochondrial reorganization may be mediating a compartmentalized cellular response. This reorganization could allow the physical interaction between the hormone-receptor complex and the enzymatic and lipidic machinery necessary for the complete steroid synthesis and release. The movement of organelles in specialized cells could impact on biological processes that include, but are not limited to, steroid synthesis.